Canada's economic assistance to the OPT: ideology, politics, and flawed responses. Issue 1 (2nd January 2021) - Dagher, Ruby
ABSTRACT: While Canada has been providing development assistance to the Palestinians in the Occupied Palestinian Territories (OPT) since 1993, its economic development assistance program took shape in 2007 after the formation of the Palestinian technocratic government. Even though the Canadian government had access to substantial analysis regarding the most significant impediments to the economic development of the OPT, its chosen areas of focus were informed more by its ideology, politics towards the region, and a belief in maintaining a viable economy until such time that efforts to work out the political issues related to illegal settlements, access and movement, borders, and the final formation of a Palestinian state bear fruit. As demonstrated, Canada's actions, along with that of other donors, have allowed for Israel to continue undertaking actions that have a significant economic cost for Palestinians and that make adequate economic development impossible and a long-term viable Palestinian economy less likely.